The trace transform for object identification - Leong, Wei Siong. (2012)
We know that Trace transform is is a novel algorithm with properties like scale and rotation invariance and occlusion robustness [1] that has been shown to be effective in recognition tasks using generalisation of Radon transform. However its computation complexity has been a problem. A Trace transform of the image is a 2D function of the parameters of each tracing line.